HPLC analysis of β-caryophyllene in copaiba oleoresin: Development, validation and applicability (Research, Society and Development, 2022)
Copaiba oil (CO) is an oleoresin containing resinous acids, comprising mainly of diterpenes, and volatile compounds, comprising of sesquiterpenes. CO has been used for many years as a therapeutic agent and cosmetic, being the β-caryophyllene (CAR) one of the main sesquiterpene markers found in CO samples. During the last years, some analytical methods have been developed for analysis of sesquiterpenes like CAR from CO. However, these methods are based on gas chromatography, and requiring additional steps, such as derivatization or extraction of the essential fraction of the CO for sesquiterpenes analysis. Liquid chromatography methodologies have been proposed only for analysis of diterpenes. Therefore, the aim of this study was to develop a high-performance liquid chromatography (HPLC) assay for CAR analysis in CO samples (Copaifera reticulata Ducke) and in emulsion systems containing CO. The HPLC system suitability was determined through the capacity factor, repeatability, relative retention, resolution, tailing factor, theoretical plate number and the height of the theoretical plate; where the method developed showed the efficiency for separation of CO compounds. The method was validated displaying specificity, linearity, precision, accuracy, and robustness. Moreover, it showed to be of utmost importance to analyze CO in emulsion systems, displaying versatile and applicability.